Combining ability and gene action for grain yield and its component traits in pearl millet (Pennisetum glaucum (L.) R. Br.) - Mungra, K. S., Dobariya, K. L., Sapovadiya, M. H. and Vavdiya, P. A. (Electronic Journal of Plant Breeding, 2015)
A line x tester analysis using six lines and eleven testers was carried out to study the combining ability and gene action for grain yield and 14 quantitative traits in pearl millet. Analysis of variance for combining ability revealed that significant differences among the mean squares was observed for lines, testers and lines x testers for all the characters except for mean squares due to lines for number of productive tillers per plant, ear head weight per plant, grain yield per plant, harvest index and threshing index and due to testers for ear head weight per plant, days to maturity, dry fodder yield per plant, grain yield per plant, harvest index and threshing index, which indicated the importance of both additive and non-additive genetic variances in the expression of these characters. The ratio of GCA variance and SCA variance indicated the predominance of non-additive gene action for the characters days to 50% flowering, length of protogyny, number of nodes per plant, plant height, number of productive tillers per plant, ear head weight per plant, days to maturity, 1000-grain weight, dry fodder yield per plant, grain yield per plant, harvest index and threshing index and additive gene action for ear head girth and ear head length. Among the lines, ICMA-04111, ICMA-92777 and ICMA-05333 and the testers J-2534, J-2454 and J-2507 displayed high gca effect for grain yield per plant and for some desirable traits. Significant and positive sca effect for grain yield per plant was displayed by the cross ICMA-05333 x J-2527 followed by ICMA-05333 x J-2340, JMSA-20064 x 283-SB-11, ICMA-92777 x STPT-115, ICMA-04999 x J-2539 and JMSA-20071 x J-2507. These crosses involved either average x average, good x poor, poor x poor or good x good general combining parents. These crosses have been identified as best hybrids for improving grain yield per plant and could be further evaluated to confirm their stable superior performance.